Protecting Crowded Places from Terrorism: An Analysis of the Current Considerations and Barriers Inhibiting the Adoption of Counterterrorism Protective Security Measures. (1st September 2020) - McIlhatton, David; Berry, James; Chapman, David; Christensen, Pernille H.; Cuddihy, John; Monaghan, Rachel; Range, Dan
Abstract: While much of the literature concerning counterterrorism focuses on policies and strategies aimed at removing either the terrorist environment and/or the groups or individuals willing to utilize political violence to achieve their goal(s), there is a much smaller body of work concerned with antiterrorism, namely those defensive measures that are designed to prevent or deter terrorist attacks. Increasingly, crowded places have become popular targets for terrorists and the research presented in this article connects the planning, design, and development of real estate with respect to the adoption of protective counterterrorism measures. It seeks to develop new understandings of the considerations that real estate developments have toward terrorism, as well as the barriers that may inhibit counterterrorism protective security measures in future development projects. The analysis is based on qualitative research, namely semi-structured interviews conducted in the United Kingdom, United States, and Australia with professionals involved in all core strands of the real estate development process. The findings suggest that considerations toward terrorism vary considerably as a consequence of a range of factors and that while expected factors such as cost and aesthetics are important determinants for decision making, a range of other barriers exist.